Iraqi Kurdish EFL teachers’ beliefs about technological pedagogical and content knowledge: The role of teacher experience and education - Ali, Sirwan Sadiq; Mohammadzadeh, Behbood (Frontiers in Psychology, 2022)
Exploring Technological Pedagogical and Content Knowledge (TPACK) has obtained considerable importance over the past two years when education needs to rely on using online learning platforms due to the COVID pandemic. Teachers' beliefs could play a determining role in their decisions and the ways they implement their knowledge. It has, however, been indicated that teachers' beliefs about TPACK in the EFL context have yet to be fully examined, especially through a mixed-methods design. To this aim, this study probed teachers' beliefs towards TPACK in general and its components in particular in Iraqi Kurdistan. Additionally, the role of teaching experience and education degree in affecting the teachers' beliefs was explored. The data was collected through a questionnaire responded by 105 EFL teachers and enriched by qualitative data gathered through a structured interview. Results showed that the teachers generally had a higher level of pedagogy and subject matter knowledge than technological knowledge. Although the quantitative data indicated that the experienced teachers had significantly higher pedagogical, content, technological, and pedagogical content knowledge than the novice teachers, the qualitative analysis revealed that novice teachers were more skilled in the utilization of technology-related knowledge domains. Additionally, it was found that Ph.D. participants had higher level of TPACK confidence than the BA ones. The results are discussed in the light of theories on teachers’ beliefs, and implications for teachers and teacher educators are presented.